Use of nebulized antimicrobials for the treatment of respiratory infections in invasively mechanically ventilated adults: a position paper from the European Society of Clinical Microbiology and Infectious Diseases. (September 2017) - Rello, J.; Solé-Lleonart, C.; Rouby, J.-J.; Chastre, J.; Blot, S.; Poulakou, G.; Luyt, C.-E.; Riera, J.; Palmer, L.B.; Pereira, J.M.; Felton, T.; Dhanani, J.; et al.
Abstract: With an established role in cystic fibrosis and bronchiectasis, nebulized antibiotics are increasingly being used to treat respiratory infections in critically ill invasively mechanically ventilated adult patients. Although there is limited evidence describing their efficacy and safety, in an era when there is a need for new strategies to enhance antibiotic effectiveness because of a shortage of new agents and increases in antibiotic resistance, the potential of nebulization of antibiotics to optimize therapy is considered of high interest, particularly in patients infected with multidrug-resistant pathogens. This Position Paper of the European Society of Clinical Microbiology and Infectious Diseases provides recommendations based on the Grading of Recommendations Assessment, Development and Evaluation (GRADE) methodology regarding the use of nebulized antibiotics in invasively mechanically ventilated adults, based on a systematic review and meta-analysis of the existing literature (last search July 2016). Overall, the panel recommends avoiding the use of nebulized antibiotics in clinical practice, due to a weak level of evidence of their efficacy and the high potential for underestimated risks of adverse events (particularly, respiratory complications). Higher-quality evidence is urgently needed to inform clinical practice. Priorities of future research are detailed in the second part of the Position Paper as guidance for researchers in this field. In particular, the panel identified an urgent need for randomized clinical trials of nebulized antibiotic therapy as part of a substitution approach to treatment of pneumonia due to multidrug-resistant pathogens.